A new versatile dropsonde for atmospheric soundings – the KITsonde - C. Kottmeier; A. Wieser; U. Corsmeier; N. Kalthoff; P. Gasch; B. Kirsch; D. Ebert; Z. Ulanowski; Z. Ulanowski; D. Schell; H. Franke; F. Schmidmer; et al. (Atmospheric Measurement Techniques)
A new modular multi-sensor aerological dropsonde system for high and fast-flying research aircraft has been developed for studying atmospheric processes. This new system allows us to drop release containers with up to four sondes inside, and data from up to 30 sondes can be transmitted simultaneously. After separation from the release container, the sondes enable high-resolution spatio-temporal profiling of temperature, humidity, and pressure with a time resolution of 1.12 s and wind of 1 s, corresponding to approximately 10 m vertical resolution. The modular design ensures simple integration of additional sensors without extensive flight tests and recertification for e.g. particle measurements and radioactivity.